Growing Science Process Skills and Student's Understanding of Physics Concepts on Bernoulli's Law Using Aeromodelling Props - S. Ida Kholida; Suprianto Suprianto; Titin Sunarti (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2021)
This study aims to analyze the effect of using aeromodelling props on the improvement of science process skills (KPS) and students' understanding of physics concepts. This research method uses Quasi-Experimental Design analysis, with sampling using purposive techniques, namely class XI IPA B as a control class and XI IPA C as an experimental class at SMA Islam An-Nidhomiyah. The instruments in this study were observation sheets and pretest post-test questions which were analyzed using the normality, homogeneity, and t-test using SPSS software. The results showed that: (1) there was a significant difference between KPS and students' understanding of physics concepts between the 2 classes with a tcount value of 2,429 (α= 0.02 < 0.05) for KPS, while the understanding of concepts obtained a tcount value of 2.677 (α 0.011 < 0.05); (2) student activity in the class that uses aeromodelling props is very active (82.5%) while those who do not use props are classified as active (68.3%). This shows that the application of aeromodelling teaching aids can grow students' KPS and understanding of physics concepts in Bernoulli's Law. Besides growing KPS and understanding physics concepts, aeromodelling students are also able to grow student learning activities in the classroom.